Perception of Electronic Examination among Undergraduate Students of University of Maiduguri (Global Journal of Human-Social Science, 2019)
The study was conducted to measure the perception of electronic examination among undergraduate students of University of Maiduguri. It was orchestrated on three specific objectives; to find out the perception of the students regarding the introduction of e-exam; to examine the perception of the students regarding e-exam as means of assessment; to examine the negative and positive perception of the students regarding the appropriateness of facilities, timing and format of question. The study employed the propositions of Technology Acceptance Model (TAM) to explain students' knowledge, acceptance and perception. The research used quantitative research method and survey methodology, using Questionnaire as instruments for data collection. The study purposely selected 200 students and found that majority of the students believe e-examination is better than the pen-paper examination. Majority of the students perceive electronic examination as an easy process.
Keywords: electronic examination; examination malpractices; information and communication technology; perception